ANALISIS PEMBATALAN AYAT AL-QUR’AN DALAM SURAT AL-NISĀ’ - Sati, Ali (IAIN Padangsidimpuan, 2020)
Even though the existence of naskh and mansūkh has always been the subject of debate among scholars, especially the understanding of one verse of the Qur'an was abolished by another verse, where Allah SWT abolished His own decree. Moving on from the pros and cons of dialectics, the writer tries to see the existence of naskh and mansukh in the Qur'an. The focus of this article is about texts and mansuk contained in surah al-Nash by using literature studies through literature-literature that discusses texts and mansukh especially in surah al-Nisa '.The author's findings, that in surah an-Nisa 'there are many verses that naskh and mansukh reach twenty-four verses, namely in verses 6, 7, 8, 9, 10, 15, 16, 17, 22, 23, 24 , 29, 33, 42, 63, 64, 71, 80, 81, 84, 90, 91, 92 and 145.